2009
DOI: 10.1158/0008-5472.can-07-6817
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Gene Expression Programs Integrate Mammalian Prostate Development and Tumorigenesis

Abstract: Studies centered at the intersection of embryogenesis and carcinogenesis have identified striking parallels involving signaling pathways that modulate both developmental and neoplastic processes. In the prostate, reciprocal interactions between epithelium and stroma are known to influence neoplasia and also exert morphogenic effects via the urogenital sinus mesenchyme. In this study, we sought to determine molecular relationships between aspects of normal prostate development and prostate carcinogenesis. We fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 47 publications
2
74
0
Order By: Relevance
“…Enrichment of embryonic gene-expression signatures has been demonstrated in multiple solid malignancies, substantiating the paradigm of embryonic reawakening in cancer and the utility of embryonic systems to model cancer progression (6,7,49). With this approach, we show that the developmental regulation of Sparcl1 expression is paralleled in prostate cancer.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Enrichment of embryonic gene-expression signatures has been demonstrated in multiple solid malignancies, substantiating the paradigm of embryonic reawakening in cancer and the utility of embryonic systems to model cancer progression (6,7,49). With this approach, we show that the developmental regulation of Sparcl1 expression is paralleled in prostate cancer.…”
Section: Discussionsupporting
confidence: 60%
“…We and others have recently illustrated that pathways essential for prostate organogenesis are reactivated in prostate cancer (6,7). During organogenesis, androgens induce epithelialmesenchymal interactions in the urogenital sinus (UGS) and drive its differentiation into a prostate (8).…”
mentioning
confidence: 99%
“…Male patient serum samples collected consecutively before and after puberty revealed that TG4 autoantibodies first arose at puberty and were sustained thereafter. This parallels TG4 expression, which begins during early puberty (8).…”
mentioning
confidence: 70%
“…The cellular origin of the hemoglobin transcripts in the 'oxygen transporter' GO term is not known, though induced expression of hemoglobin has been reported in nonerythroid cells such as macrophages and in the developing prostate. 24,25 Validation in a small set of independent samples was performed. Though the small sample size may have contributed to the lack of statistically significant differences ( Figure 5), we observed the consistent trend of lower expression of stress-induced genes in LRP cases.…”
Section: Discussionmentioning
confidence: 99%